(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze the structure of cardiovascular drugs awarded in bidding for medical facilities in Vietnam during the period 2019-2023. Materials and methods: A descriptive study was conducted on active ingredients classified in the cardiovascular drug group based on the official lists of awarded bids published by the Drug Administration of Vietnam from January 2019 to December 2023. Results: During the period 2019-2023, the number of winning lots and the value of cardiovascular drugs in tenders fluctuated significantly, with decreases of 61.6% and 80.3% respectively in 2020, followed by a recovery in 2021 and stabilization in the last two years. Compared to 2019, the average in the stable period (2022-2023) saw an increase of 51.4% in the number of winning lots but a decrease of 19.2% in tender value. By pharmacological groups, antihypertensive drugs dominated (around 60%), followed by lipid-lowering drugs (about 15%). Generic drugs overwhelmingly dominated and showed an increasing trend in tender value share from 63.16% (2019) to a peak of 84.75% (2020), while original brand drugs declined gradually. Regarding origin, domestically produced drugs tended to increase their proportion, with tender value rising from 28.90% (2019) to 40.61% (2023) after peaking at 45.85% (2020). In terms of formulation composition, the tender value share of multi-ingredient drugs increased from 19.01% (2019) to 34.39% (2020) and remained stable between 29.16% and 32.35% in subsequent years. Conclusion: The cardiovascular drug market in Vietnam underwent major fluctuations during 2019-2023 due to the combined impact of COVID-19 pandemic and bidding regulations. Antihypertensive and lipid-lowering drug groups held an absolute dominance. The market structure shifted clearly toward generic drugs and domestically manufactured medicines, along with an increasing trend in the use of multi-ingredient drugs.